The Dual-Edged Sword: Generative AI, Theological Bias, and the Global Challenge of Countering Violent Extremism - Abbas, Muhammad Hassan; Ahmad, Dr. Sajjad; Imam, Muhammad Asim (South Asian Journal of Religion and Philosophy (SAJRP), 2025)
Generative AI, such as ChatGPT, DeepSeek, and deepfakes, plays a complex dual role in both advancing and combating online extremism, raising critical ethical and theological questions. While extremist entities exploit AI for recruitment and ideological dissemination, counter-extremism initiatives are increasingly using AI to identify and disrupt radical content. This article explores this tension and discusses illustrative case studies to show how online radicalization can lead to real-world violence. It also addresses theological concerns about AI’s interpretation of sacred texts, which may reflect biases across various religious traditions, including Islam, Christianity, Judaism, and Hinduism. The paper proposes the formation of "Ethical AI Oversight Committees" comprising religious scholars, technologists, and policymakers to ensure a balanced approach that safeguards security, religious liberty, and cultural diversity. Integrating perspectives from AI ethics, religious studies, and policy, this study advocates for a proactive, ethically guided digital environment to counter the threat of violent extremism.